2013
DOI: 10.3917/g2000.301.0035
|View full text |Cite
|
Sign up to set email alerts
|

Les composantes de la relation dans les e-services : comment créer la fidélité à l'égard d'un portail Internet ?

Abstract: Distribution électronique Cairn.info pour Association de recherches et publications en management. © Association de recherches et publications en management. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Chiou (2004) found overall satisfaction of consumers for internet access positively influencing their commitment. Allagui and Temessek (2004) showed that the more customers are satisfied with their experience with a provider of e-service, the more committed they will be. Thus, it is hypothesised that:…”
Section: Review Of Literaturementioning
confidence: 99%
“…Chiou (2004) found overall satisfaction of consumers for internet access positively influencing their commitment. Allagui and Temessek (2004) showed that the more customers are satisfied with their experience with a provider of e-service, the more committed they will be. Thus, it is hypothesised that:…”
Section: Review Of Literaturementioning
confidence: 99%